Driven by data : a practical guide to improve instruction - Bambrick-Santoyo, Paul, 1972- (San Francisco : Jossey-Bass, 2010)
An exploration of data-based methods and challenges of the implementation of data-driven instruction that offers tips and guidelines and includes twenty case studies and a CD-ROM with instructional tools.
Professional
System requirements not stated.
Includes bibliographical references (p. [281]-287) and index.
Professional.
teacher library resource.
Keywords: Education -- United States -- Data processing -- Case studies; Educational tests and measurements -- United States -- Case studies; Educational evaluation -- United States -- Case studies; School improvement programs -- United States -- Case studies; School management and organization -- United States -- Case studies; Education -- United States -- Data processing -- Case studies; Educational tests and measurements -- United States -- Case studies; Educational evaluation -- United States -- Case studies; Schools -- Administration -- United States -- Case studies